PENYEBAB TINGGINYA ANGKA PERNIKAHAN DINI PADA REMAJA PUTRI DI KECAMATAN BATU AMPAR - Aznidawati, Charli; Yulfar, Arlan; Sulistyawati, Tri Ribut (Universitas Batam, 2021)
Early marriage according to BKKBN is marriage under the age of 20 years which is mentioned by social factors, education, economy, culture, the role of parents, oneself and place of residence. Early marriage has a bad impact on health, especially the immature female reproductive organs. The purpose of the study was to determine the cause of the high rate of early marriage. This type of quantitative research using a descriptive research design was carried out in Batu Ampar District in August 2020. The population of teenagers who had early marriages in Batu Ampar District during January and February 2020. The sample in this study was 37 teenagers. The sampling technique in this study was Total sampling. The instrument used was a questionnaire. The results of the study found that the cause of the high rate of early marriage is the lack of knowledge of adolescents as much as 67.6%, parents who do not play a role as much as 91.9%, attitudes that support early marriage as much as 75.7%. The conclusion that causes the high rate of early marriage is knowledge, the role of parents, and attitudes towards the occurrence of early marriage. Suggestions for the community to provide information about the impact of early marriage.